Bioanalysis of acetylcarnitine in cerebrospinal fluid by HILIC–mass spectrometry. (24th February 2015) - Holder, Brian R.; McNaney, Colleen A.; Luchetti, David; Schaeffer, Eric; Drexler, Dieter M.
Abstract Acetyl‐l‐carnitine (ALCAR) is a potential biomarker for the modulation of brain neurotransmitter activity, but is also present in cerebrospinal fluid (CSF). Recent studies have utilized hydrophilic interaction liquid chromatography–tandem mass spectrometry (HILIC‐MS/MS) based assays to detect and quantify ALCAR within biofluids such as urine, plasma and serum, using various sample pretreatment procedures. In order to address the need to quantify ALCAR in CSF on a high‐throughput scale, a new and simple HILIC‐MS/MS assay has been successfully developed and validated. For rapid analysis, CSF sample pretreatment was performed via 'dilute and shoot' directly onto an advanced HILIC column prior to MS/MS detection. This newly developed HILIC‐MS/MS assay shows good recoveries of ALCAR without the need for chemical derivatization and multistep sample extraction procedures. The employment of this assay is suitable for the high‐throughput bioanalysis and quantification of ALCAR within the CSF of various animal models and human clinical studies. Copyright © 2015 John Wiley & Sons, Ltd.